METHANE DRY REFORMING OVER MONTMORILLONITE SURFACE MODIFICATION SUPPORTED NICKEL CATALYST - Chaisamphao, Juthasiri; Kiatphuengporn, Sirapassorn; Faungnawakij, Kajornsak; Donphai, Waleeporn (MATTER: International Journal of Science and Technology, 2019)
Dry reforming of methane has been taken an interest in research and development for converting greenhouse gases (CH4 and CO2) into hydrogen (H2) and carbon monoxide (CO). Clay has been considered as promising materials because of their structure, low cost and wide availability. Different surface modifications of clay directly affect the performance of catalyst in term of CH4 and CO2 conversion. This research studied nickel loaded on montmorillonite (MMT) clay support with different surface modifications on the activity in dry reforming of methane in fixed-bed reactor with reactant gases flow rate of 60 ml/min (CH4:CO2 of 1) at reaction temperature ranges of 500 – 800°C. Montmorillonite clay support with different surface modifications including trimethyl stearyl ammonium (MMT-TSA), dimethyl dialkyl amine (MMT-DDA), methyl dihydroxy-ethyl hydrogenated tallow ammonium (MMT-MDA) and aminopropyltriethoxysilan and octadecylamine (MMT-AO) were investigated. As the results, the performances of all catalysts increased with increasing reaction temperature because this reaction is endothermic reaction. Among them, Ni/MMT-TSA catalyst exhibited the highest CH4 and CO2 conversions at all reaction temperatures due to its high surface area, and high metallic surface area.